Synthesis of nanofluid to improve heat transfer in annular concenteric heat exchanger / Seyedeh Maryam Hosseini - Seyedeh Maryam , Hosseini (2017)
Traditional heat exchanger liquids (e.g., water, ethylene glycol, oil and etc.) possess inherently low heat transfer performance as a consequence of their low thermal conductivities. In recent past, there has been remarkable interest in employing nanofluids (nano-coolants) for increasing thermal performance of these liquids. Nano-coolants taken under investigation in this research were aqueous suspensions of highly conductive nanoparticles in Distilled water (DI water) which provided enhanced thermal properties at even lower nanoparticle concentrations and were employed in different thermal applications such as solar collectors, heat exchangers and electronic cooling systems. The current study highlighted experimental study convective heat transfer as well as friction loss of clove-treated multi-walled carbon nanotubes (C-MWCNTs) and clove-treated graphene nanoplatelets (CGNPs) water based nano-coolants flowing in an annular concentric heat exchanger under turbulent and constant heat flux conditions. The multi-walled carbon nanotubes (MWCNTs) were functionalized covalently in one-pot using free radical reaction in a green and scalable way followed by dispersing the C-MWCNTs in base fluid at various weight concentrations. The functionalized Carbon nanotubes were characterized using, thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy, and transmission electron microscopy (TEM). UV-vis spectroscopy was employed to confirm the stability of the nanofluids in DI water. Further, Zeta potential had provided also proof of the presence of hydrophilic groups in the functionalized nanoparticles. The thermo-physical properties of nanofluids have shown a good enhancement compared to that of the base fluid which refers to their application as suitable heat exchanger liquids. The heat transfer and friction loss were studied experimentally in a flow loop with a concentric annular test section subjected to a constant heat flux of 38346 W/m2, at the Reynolds number range of 3055 ± 5 to 7944 ± 5. Numerical simulation was performed as an approximating procedure for prediction of the results in this study. Single-phase mixture model was considered for simulation of the nanofluids flow in three dimensional annular heat exchanger. Primary experiments were performed with the base fluid and the results of the average Nusselt numbers obtained from the experimental were compared with those calculated using empirical equations of Gnielinski and Petukhov, and the results have shown 4 and 9 %, error respectively, within 95% confidence level, which indicates a well reliability and accuracy of the data obtained from the experimental test section. Moreover, convective heat transfer experiments were performed for the nanofluids in annular heat exchanger at the constant heat flux of 38346 W/m2 at fully developed flow. The data show that addition of low amount of functionalized MWCNTs to the DI base fluid notably elevates its convective heat transfer coefficient compared to that of the DI water. However, there was only small increment in friction factor compared to the data from water alone for all the tested nanofluids. It is worth noting that the significant increment of the performance index and its upward trend compared to that of water represents all the nano-coolants have strong potential for use as effective heat transfer working fluids in various thermal applications.